Addressing the treatment of macrophage activation syndrome: A challenging balance between immune suppression and infectious risk - Vassia V; Iannaccone A; Marengo S; Briozzo A; Brussino A; Alessi L; Brussino L; Norbiato C (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2022)
Hemophagocytic Lymphohistiocytosis (HLH) is a rare and potentially life-threatening syndrome related to a dysregulation of cytolytic function of Natural Killer (NK) cells and cytotoxic T cells (CTLs), which in turns leads to an inappropriate immune stimulation and hyperinflammatory state, resulting in hypercytokinemia, accumulation of activated lymphocytes and macrophages [1,2].